2022
DOI: 10.3390/molecules27248884
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Effect and Inhibition of the Virulence Mechanism of D-Limonene against Candida parapsilosis

Abstract: Yeasts from the Candida parapsilosis complex are clinically relevant due to their high virulence and pathogenicity potential, such as adherence to epithelial cells and emission of filamentous structures, as well as their low susceptibility to antifungals. D-limonene, a natural compound, emerges as a promising alternative with previously described antibacterial, antiparasitic, and antifungal activity; however, its mechanisms of action and antivirulence activity against C. parapsilosis complex species have not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Furthermore, the upregulation of the STI1 domain, known for its role in various cellular processes, including the transfer of hydrophobic substrates and the DNA damage response, suggests that ISO's antifungal action also involves DNA damage in C. tropicalis. Our results are in accordance with previous studies in C. tropicalis and C. parapsilosis, where terpenes like D-limonene have exhibited multiple action targets [24,25,103].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the upregulation of the STI1 domain, known for its role in various cellular processes, including the transfer of hydrophobic substrates and the DNA damage response, suggests that ISO's antifungal action also involves DNA damage in C. tropicalis. Our results are in accordance with previous studies in C. tropicalis and C. parapsilosis, where terpenes like D-limonene have exhibited multiple action targets [24,25,103].…”
Section: Discussionsupporting
confidence: 93%
“…Regrettably, the three principal antifungal drug classes (polyenes, echinocandins, and azoles) have been unable to stem the surge in life-threatening fungal infections observed over the past few decades [22]. In response to this pressing clinical challenge, compounds derived from botanical sources have gained traction as a promising alternative [23][24][25]. In our previous investigations, we established that isoespintanol (ISO), a monoterpene derived from Oxandra xylopioides, exhibits potent antifungal properties against Candida tropicalis [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…and A. fumigatus [59][60][61][62][63]. Several studies reported the antifungal effect of limonene against Candida spp., A. fumigatus, T. rubrum and several other fungi [60,[64][65][66][67][68][69][70]. In contrast, borneol presented a very weak activity against several fungal strains [60,[71][72][73][74].…”
Section: Discussionmentioning
confidence: 98%
“…And for fungi, it was shown that D-limonene induced disruption of the specific cell differentiation program of C. parapsilosis, leading to apoptosis, and also arrested the cell cycle of C. albicans in the G1 phase and the abundancies of 52 proteins were significantly changed (≥two-fold), 33 of which were upregulated and 19 downregulated. Furthermore, qPCR demonstrated that C. albicans cell wall and cell membrane damage stress genes (KRE 9, ERG 11), oxidative stress genes (TRR 1), nucleolus stress genes (PRL 11), and apoptosis-related genes (CaMCA 1) were overexpressed, indicating that D-limonene can induce apoptosis in C. albicans cells through multiple pathways [85,93].…”
Section: Interference With Gene Expressionmentioning
confidence: 99%